2010
DOI: 10.1038/nm.2278
|View full text |Cite
|
Sign up to set email alerts
|

Histamine deficiency promotes inflammation-associated carcinogenesis through reduced myeloid maturation and accumulation of CD11b+Ly6G+ immature myeloid cells

Abstract: Histidine decarboxylase (HDC), the unique enzyme responsible for histamine generation, is highly expressed in myeloid cells but its function is poorly understood. Here, we show that Hdc knockout mice exhibit a markedly increased rate of colon and skin carcinogenesis. Using Hdc-EGFP BAC transgenic mice, we demonstrate that Hdc is expressed primarily in CD11b+Ly6G+ immature myeloid cells (IMCs) that are recruited early on in chemical carcinogenesis. Transplant of Hdc-deficient bone marrow to wildtype recipients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
227
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 195 publications
(238 citation statements)
references
References 47 publications
11
227
0
Order By: Relevance
“…An example of this was shown in mice with chemically induced cancer crossed with histamine-deficient mice, where the lack of histamine stalled differentiation of immature neutrophils and increased tumor incidence and growth 75 . These data suggest that immature cells have independent functions from mature neutrophils.…”
Section: Neutrophil Retention and Release From Bone Marrowmentioning
confidence: 99%
“…An example of this was shown in mice with chemically induced cancer crossed with histamine-deficient mice, where the lack of histamine stalled differentiation of immature neutrophils and increased tumor incidence and growth 75 . These data suggest that immature cells have independent functions from mature neutrophils.…”
Section: Neutrophil Retention and Release From Bone Marrowmentioning
confidence: 99%
“…It has been known that monocyte-derived myeloid suppressor cells can suppress the anti-tumor activity of T-cells by producing IL-10. In an experimental model of chemical-induced carcinogenesis, histidine carboxylase (HDC)-deficient mice showed a severe tumor progressive phenotype [36], accompanied by a massive influx of CD11b + Gr-1 + monocytes and their impairment in maturation. An independent study revealed that vascular endothelial growth factor (VEGF) produced by the infiltrating Gr-1 + monocytes in mammary cancer promotes tumor metastasis [37] into the lung.…”
Section: Tumor Progressionmentioning
confidence: 99%
“…Yang et al (7) observed an increased accumulation of immature CD11b + /Gr1 + myeloid cells during cancer progression in HDC 2/2 mice compared with HDC-sufficient mice and reported that HDC 2/2 mice were strikingly susceptible to chemically induced cancer. These investigators also reported that the exogenous administration of histamine to HDC 2/2 mice prevented the accumulation of immature myeloid cells (7). However, the detailed mechanisms by which histamine deficiency results in the accumulation of immature myeloid cells are largely unknown.…”
mentioning
confidence: 99%